Control efficiency of hexaconazole-lentinan against wheat sharp eyespot and wheat crown rot and the associated effects on rhizosphere soil fungal community - Yang, Xiu; Zhang, Zhongxiao; Yuan, Yazhen; Wang, Kaiyun; Chen, Yuan; Wang, Hongyan (Frontiers in Microbiology, 2022)
The use of polysaccharides to induce the systemic immune response of plants for disease resistance has become an effective plant protection measure. Sharp eyespot wheat and crown rot wheat are serious diseases of wheat. In this study, the control effects of hexaconazole and LNT seed dressing of the two wheat diseases were evaluated by field experiments, the effects of the seed dressing on plant growth, soil enzyme activity and community diversity in the wheat rhizosphere were discussed. The results showed that the combined seed dressing of hexaconazole at 0.5 a.i. g·100 kg-1 and LNT at 4 a.i. g·100 kg-1 could significantly improve the control effect of the two wheat diseases. The combined treatment of hexaconazole and LNT had little effect on wheat soil enzyme activities. Different seed dressing treatments changed the fungal community structure in the wheat rhizosphere soil, and the combination of LNT and hexaconazole reduced the relative abundance of Rhizoctonia, Cladosporium, Fusarium, Bipolar and Gibberella in wheat planting soils. Soil-borne diseases of wheat are effectively controlled.